Homoseksual Sebagai Fenomena Patologi Sosial: Tinjauan Norma Sosial - Ariani, Rahma; Khadijah (Jurnal Dinamika Sosial Budaya, 2025)
Homosexuality as a phenomenon of social pathology within the context of prevailing social norms in society, particularly in Indonesia. Homosexuality is viewed as deviant behavior that violates social, cultural, and religious norms. These norms continue to face challenges from social changes, where LGBT (lesbian, gay, bisexual, transgender) behavior is seen as one of the symptoms of such changes. The study employs a qualitative method based on literature reviews to understand the relationship between homosexuality and social norms, as well as its impact on society. The findings show that homosexuality, often considered a form of social pathology, generates social anxiety and negative reactions, including discrimination and exclusion. The factors contributing to homosexuality include environmental influences, past trauma, and biological factors. From religious and cultural perspectives, homosexual behavior is rejected, while psychologically, individuals with egodystonic homosexuality experience significant mental stress. Although homosexuals are recognized as having basic human rights as citizens, there is no clear regulation regarding their sexual activities in Indonesia. This study contributes to a deeper understanding of homosexuality as a social phenomenon and offers approaches to addressing this issue without neglecting the human rights of LGBT individuals.